Analisis Sentimen Pada Twitter @Ovo_Id dengan Metode Support Vectore Machine (SVM) - Sulastomo, Hendri; Ramadiansyah, R; Gibran, Khalil; Maryansyah, Efrian; Tegar, Aththoriqh (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Social networking helps internet users communicate. This is because social network users can convey messages by utilizing the facilities prepared by each social media. Social media users' messages can be used in various ways, such as a review of a product or a review of a problem in politics or current social problems. This can be done by analyzing the sentiments of social media users. The support vectore machine method is one method that can be used to analyze sentiment. In sentiment analysis using the support vectore machine method, it is done by classifying sentiment into compliant or not compliant classes. The accuracy rate of sentiment analysis for @Ovo_ID using the support vectore machine method is 94% using 1000 tweet data.